Smile designing using recurring esthetic dental proportion and aesthetic pre-evaluative temporary technique with porcelain laminate veneers: a case report - Nipane, Ronika; Sundarkar, Pravin; Thombare, Bhagyashree; Dammani, Brajesh; Wankhade, Bhushan; Shambharkar, Sonali; Ajmire , Samiksha (International Journal of Research in Medical Sciences, 2023)
Beautiful confident smile has a positive impact on the psychosocial well-being of patients. Spacing present in the anterior region makes a patient feel dissatisfied with their smile. Over the years, a number of innovative techniques have been described in the treatment of patient having spaces between teeth in the anterior region. However, a less invasive and short-time treatment procedure with satisfactory result is preferred by the patient. Laminates have a unique position in today’s dental practice. These conservative restorations are especially important for young permanent dentitions. Porcelain veneers can be considered to be very much in cosmetic dentistry because they deal innumerable advantages over any previous form of veneering systems. This case report described the technique of closure of spaces between teeth in the anterior region by applying recurring esthetic dental (RED) proportion and aesthetic pre-evaluative temporary (APT) technique for smile designing using laminates. The RED proportion has been stated to be an essential tool for achieving esthetics and harmony in smile. The APT technique facilitated diagnosis, communication, and preparation, providing predictability for the restorative treatment. Limiting the preparation depth to the enamel surface significantly increases the performance of porcelain laminate veneers.